Families of blowups of the real affine plane: Classification, isotopies and visualization. (May 2021) - Brodmann, Markus; Schenzel, Peter
Abstract: We classify embedded blowups of the real affine plane up to oriented isomorphy. We show that two blowups in the same isomorphism class are isotopic, using a matrix deformation argument similar to an idea given in Shastri (2002) . This answers two questions which were motivated by the interactive visualizations of such blowups (see Schenzel and Stussak, 2013, Stussak, 2007, 2013 ).